DETERMINATION OF LDL AND HDL IN SUBJECTS WITH HIGH SERUM CHOLESTEROL LEVELS AND THEIR RELATION WITH AGE, SEX AND BODY MASS INDEX - VAKILI, Z.; HOSSEINI, M. ESHAGH; TALARI, S.A.; MOUSAVI, G.H.; FAKHARIAN, E.; MOSHTAGHI, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Hypercholesterolemia is a major risk factor for Ischemic Heart Disease (IHD). Since this disease has had an increasing number in Iran in the past few decades, the present study was designed to measure the level of low density lipoprotein (LDL) and high density lipoprotein (HDL) in subjects with cholesterol level above 200mg/dL and also to evaluate its relation with age, sex and body mass index (BMI). This descriptiveanalytic study carried on 283 subjects (56 diabetic and 227 non-diabetic) in Kashan. After 12 hours fasting, venous blood sample was obtained for measurement of cholesterol level. A questionnaire including age, sex, history of diabetes, height and weight was completed. HDL and LDL were measured in subjects with cholesterol level above 200mg/dL. Tests were done by RA-1000 Analyzer and Man company kits and results were recorded. Data was analyzed with statistical tests. Of 283 subjects 27.2% were males and 72.6% females. Fifty-two and six percent were in age group 20 to 50 and others in the age group above 50. In males both diabetic and non-diabetic groups LDL was significantly higher than females (p<0.05). HDL was lower but not significant. With increasing age LDL level increased significantly in non-diabetics (P<0.05) but in diabetics the difference was not significant. HDL in both diabetics and non-diabetics in different age groups showed no significant difference. In non-diabetics with increasing BMI, LDL level increased significantly (p < 0.05), and HDL decreased non significantly. In diabetics increase of LDL and decrease of HDL was significant (p < 0.05). The study revealed that aging, male gender and obesity cause increase in LDL level and decrease in HDL level. Since these are risk factors for IHD and other vascular diseases, regular measurement of HDL and LDL is recommended in the above mentioned groups.